Impact of tailored anti-P2Y12 therapies in acute coronary syndromes. (April 2015) - Stimpfle, Fabian; Geisler, Tobias
Acute coronary syndromes are a major disease burden and the prognosis has improved over the last decades due to improvement of medical and interventional treatments. Novel P2Y12 -ADP-receptor antagonists have been introduced into clinical treatment offering more potent and rapid onset of action with the downside of increased bleeding risk. This special report will focus on interindividual variability of antiplatelet drugs in the setting of acute coronary syndromes and the current impact and potential future of point-of-care testing to personalize therapy aiming to improve prognosis in acute coronary syndrome patients.